PROFILAKSIS PRA-PAJANAN (PPrP) HIV/AIDS PADA LELAKI SEKS LELAKI - Teddy Tjahyanto; Natasha Cita Paradhita Kusuma; Agnes Marcella; Gladys Ariella; Alicia Sarijuwita (Universitas Pahlawan, 2022)
Introduction: HIV is an infection that attacks the immune system which is characterized by a decrease in CD4+ cells with MSM as the 2nd largest contributor globally. PPrP serves as an additional option in the prevention of HIV-negative MSM from becoming infected with HIV. Objective: This study was conducted to review more deeply the role of pre-exposure prophylaxis in reducing the risk of contracting HIV in male sex groups with HIV negative men and to review the effectiveness and implementation of HIV/AIDS pre-exposure prophylaxis in male sex men so that it is expected to be a consideration in efforts to combat HIV/AIDS. Methods: Literature search was conducted from journal articles published online in the period 2012-2021. The databases used are ScienceDirect, Pubmed, Google Scholar, and Cochrane. Results: The study showed that the factors that significantly affected the high prevalence of HIV cases among MSM were anal sex and based on the findings the use of PrEP showed a significant effectiveness for the MSM group with pre-exposure prophylaxis as a preventive measure in dealing with HIV positive cases. Conclusion: PrEP has been shown to significantly reduce the risk of contracting HIV in HIV-negative MSM groups and has the potential to be an additional prevention option so that it can be applied in efforts to prevent HIV infection and reduce the spread of HIV in MSM.